2023
DOI: 10.1038/s41598-023-41744-8
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion and characterization of recycled polyethylene terephthalate (rPET) filaments compounded with chain extender and impact modifiers for material-extrusion additive manufacturing

Ola Rashwan,
Zachary Koroneos,
Trent G. Townsend
et al.

Abstract: The continuous growth of annual production and consumption of polyethylene terephthalate (PET) is coined with increasing waste that leaks into the environment, landfills and oceans as microplastics and nano plastics fragments. Upcycling the recycled PET to make a feedstock for the fast-growing material-extrusion additive manufacturing (MEX-AM) technology can contribute to the solution and supports the concept of sustainable materials. In this work, extrudable filaments comprising recycled polyethylene terephth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Rashwan et al explained that only one degradation peak is found around 420 C, indicating that the additives did not negatively impact the decomposition temperatures. 49…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Rashwan et al explained that only one degradation peak is found around 420 C, indicating that the additives did not negatively impact the decomposition temperatures. 49…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Therefore, Rashwan et al demonstrated the utilization of recycled PET (rPET) as sustainable value-added material feedstock for material-extrusion additive manufacturing technology. For this, rPET was compounded with low-cost additives such as pyromellitic dianhydride (PMDA, a chain extender), maleic anhydride-functionalized styrene-ethylene-butylene-styrene terpolymer (MA-g-SEBS, a thermal modifier/toughening agent), ethylene-ethyl acrylate-glycidyl methacrylate terpolymer (E-EA-GMA, a reactive elastomeric impact modifier), and ethylene-ethyl-acrylate (EEA, non-reactive elastomeric impact modifier), and extruded into filaments using twin-screw extruder for potential application in prototyping, tooling and testing parts, or end-use internal parts of small machines and cars 10 . In another approach, Verma et al .…”
Section: Collection Overviewmentioning
confidence: 99%
“…Polyethylene Terephthalate (PET) Easy Packaging, textiles, electronic cables, water bottles [32][33][34][35][36][37][38][39][40] High-Density Polyethylene (HDPE) Easy Pipes, chemicals packaging, fuel tanks, bumpers [41][42][43][44][45][46] Polyvinyl Chloride (PVC) Moderate Bags, medical equipment, pipes [47] Low PET is usually used in AM by employing material extrusion (MEX) processes such as fused filament fabrication (FFF), but several challenges have emerged due to its shrinkage and warpage issues caused by high fusion temperatures and lack of control of crystallinity, water absorption (leading to molecular weight reduction) and weak interfacial bonding between layers [32][33][34][35]. PET is mainly used for water and food packaging and the waste-tofeedstock process consists of label removal, water cleaning and drying, and granulation or shredding into flakes or pellets before sterilization.…”
Section: Recycling Symbol Plastic (Acronym) Recyclability Applicationsmentioning
confidence: 99%
“…PET is mainly used for water and food packaging and the waste-tofeedstock process consists of label removal, water cleaning and drying, and granulation or shredding into flakes or pellets before sterilization. Single-or twin-screw extruders are commonly used for feedstock production [36][37][38][39][40]. Polyethylenes (HDPE and LDPE) are used as well in the same industry, with HDPE providing a high strength-to-density ratio and being employed for blow-molded water bottles.…”
Section: Recycling Symbol Plastic (Acronym) Recyclability Applicationsmentioning
confidence: 99%
See 1 more Smart Citation